In vitro transcription in E. coli crude lysates prepared on cellophane discs. - Valla, S (1978)
An in vitro RNA-synthesizing system consisting of gently lysed E. coli cells on cellophane discs is described. The system has been optimalized with respect to total RNA synthesis. Under certain standard conditions DNA dependent RNA polymerase (EC 2.7.7.6) is responsible for the majority of the RNA synthesis. The extensive rifampicin sensitivity of the synthesis indicates that most of the transcripts are initiated in vitro. The RNA synthesizing system described here has been developed with the aim of studying phage transcription in vitro. We show here that lysates of a P4 infected P2 lysogen support initiation and propagation of transcription from the P2 prophage.